Elective Surgery Service of Oncology Surgery Division Before and During Early Pandemic Era of Corona Virus Disease 19 (COVID-19) in Dr. M. Djamil Hospital Padang - Maisa Fitra; Wirsma Arif Harahap; Yevri Zulfiqar (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Introduction Corona Virus Disease 19 (COVID-19) infection was first reported inWuhan, China, in December 2019. The author wants to know how the OncologySurgery Division elective surgery patient services before and during early pandemi cera of COVID-19 at Dr. M Djamil Padang Hospital. M ethod: This research is acomparative study with a quantitative approach to elective surgery patients in theOncology Surgery Division before and during early pandemic era of COVID-19 at Dr.M Djamil Padang Hospital. The sampling technique in this study was total sampling.Data analysis will be carried out using statistical analysis in accordance with theexisting data scale and using SPSS software. Results: In this study, 137 sampleswere obtained consisting of 80 samples before the COVID-19 pandemic and 57samples during early pandemic era of COVID-19. Of the 57 patients who underwentelective surgery from the Surgical Oncology Division during early pandemic era ofCOVID-19, all patients were not suspicious / confirmed. The time for oncologyservice assessment was 14.26 days before COVID-19 pandemic and 8.93 days duringearly pandemic era of COVID-19. Conclusion: More patients who underwent electivesurgery in the surgical oncology division were female, both before and during earlypandemic era of COVID-19. The mean age of patients before COVID-19 pandemicwas 48.72 years and 49.53 years during early pandemic era of COVID-19. There isa disparity between the length of time the assessment of elective surgery patients inthe surgical oncology division before and during early pandemic era of COVID-19pandemic.